Konsep “Entrepreneur’s Dream” pada Desain Interior Inkubator Bisnis dan Teknologi Universitas Kristen Petra - Fanny Wijaya; Mariana Wibowo; M. Taufan Rizqy (Universitas Negeri Medan, 2020)
The interior design of the Petra Christian University Business and Technology Incubator aims to provide a forum for the people of East Java, especially start-up companies, students, lecturers and the outside community to start their start-ups and to develop the creative economy in East Java. The current interior of IBT Petra still uses former classrooms. So that it still does not accommodate the activities and needs of its users to work optimally and creatively. In order to solve the problem formulation, the Design Thinking 101 method is used, which consists of 3 main stages, namely Understand (Collecting and Analyzing Data), Explore (Looking for ideas for problem solving) and Materialize (Testing and developing designs). Then an IBT interior design was produced with the concept of Entrepreneur's Dream, which applies the vision, mission and goals of a startup, namely innovative, grow, caring, global into its interior design that can help realize the vision and mission. The resulting scope includes creative co-working space, exhibition space, store, office, event space, makerspace and café.